MODEL PEMILIHAN MEDIA PEMBELAJARAN BERBASIS TIK BERDASARKAN KARAKTERISTIK MATERI DAN TUJUAN PEMBELAJARAN - Budi, Budi Rahrajo; Lia, Lia Kurnia Asih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The integration of Information and Communication Technology (ICT) into education has become an essential component of twenty-first-century learning. However, many teachers still face challenges in selecting instructional media that align with learning materials, instructional objectives, learner characteristics, and available technological resources. This study aims to develop a conceptual model for selecting ICT-based instructional media based on the characteristics of learning materials and instructional objectives to support teachers' decisionmaking processes. The study employed a qualitative descriptive approach using a library research method by analyzing and synthesizing scholarly books, national and international journal articles, conference proceedings, and educational policy documents. Content analysis was applied to identify the key factors influencing the selection of ICT-based instructional media. The findings reveal that the selection of instructional media is influenced by four main factors: learning material characteristics, instructional objectives, learner characteristics, and the availability of technological infrastructure. Based on the synthesis of the literature, this study proposes a conceptual model that integrates these four factors into a systematic decision-making framework for selecting ICT-based instructional media. The proposed model emphasizes that instructional media selection should be considered an integral part of instructional design rather than merely the adoption of advanced technology. Consequently, the model is expected to assist teachers in selecting instructional media that are pedagogically appropriate, contextually relevant, and effective in improving learning quality while supporting the implementation of twenty-first-century education.